Do Genetic Polymorphisms Affect Fetal Hemoglobin (HbF) Levels in Patients With Sickle Cell Anemia Treated With Hydroxyurea? A Systematic Review and Pathway Analysis - Sales, Rahyssa Rodrigues; Nogueira, Bárbara Lisboa; Tosatti, Jéssica Abdo Gonçalves; Gomes, Karina Braga; Luizon, Marcelo Rizzatti (Frontiers in Pharmacology, 2022)
Hydroxyurea has long been used for treatment of sickle cell anemia (SCA), and its clinical effectiveness is related to induction of fetal hemoglobin (HbF), a major modifier of SCA phenotypes. However, there is substantial variability in response to hydroxyurea among patients with SCA. While some patients show an increase in HbF levels and ameliorate clinical condition under low doses of hydroxyurea, other patients present a poor effect or even develop toxicity. However, the effects of genetic polymorphisms on increasing of HbF levels in response to hydroxyurea in patients with SCA (Hb SS) has been less explored. Therefore, we performed a systematic review to assess whether single nucleotide polymorphisms (SNPs) affect HbF levels in patients with SCA treated with hydroxyurea. Moreover, we performed pathway analysis using the set of genes with SNPs found to be associated with changes on HbF levels in response to hydroxyurea among the included studies. The systematic literature search was conducted in Medline/PubMed, EMBASE, Cochrane Central Register of Controlled Trials, CINAHL (Cumulative Index to Nursing and Allied Health Literature), Scopus and Web of Science. Seven cohort studies were included following our inclusion and exclusion criteria. From the 728 genetic polymorphisms examined in the included studies, 50 different SNPs of 17 genes were found to be associated with HbF changes in patients with SCA treated with hydroxyurea, which are known to affect baseline HbF, but are not restricted to them. Enrichment analysis of this gene set revealed Reactome pathways with the lowest adjusted p-values and highest combined scores related to VEGF ligand-receptor interactions (R-HSA-194313; R-HSA-195399) and urea cycle (R-HSA-70635). Pharmacogenetic studies of response to HU therapy in patients with SCA are still scarce and markedly heterogeneous regarding candidate genes and SNPs examined for association with HbF changes and outcomes, suggesting that further studies are needed. The reviewed findings highlighted that, similar to baseline HbF, changes on HbF levels upon HU therapy are likely to be regulated by multiple loci. There is evidence that SNPs in intron 2 of BCL11A affect HbF changes in response to HU therapy, a potential application that might improve the clinical management of SCA.